Fibrodysplasia ossificans progressiva: A case report - Vasala, Sreedhar; Rao, V Dharma; Reddy, M Rajaneesh; Reddy, P Ramyatha; Murali, K (Asian Journal of Medical Sciences, 2014)
Fibrodysplasia ossificans progressiva (FOP) is a genetic disorder with unknown cause. Disease is characterized by heterotopic ossifications of connective tissue and congenital malformations of distal part of extremities. Most cases are sporadic and transmitted as autosomal dominant. As very few cases of FOP are being reported in Indian literature, we, therefore, report one such case here. Our case is a 20 years-old female patient who had bilateral short great toes with hallux valgus associated with heterotopic ossifications of connective tissue with restrictions of range of motion and disability of daily living activities. We have diagnosed it as FOP based on our physical examination and skeletal x-rays findings. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9915 Asian Journal of Medical Sciences 2014 Vol.5(4); 113-115